1996
DOI: 10.3168/jds.s0022-0302(96)76492-5
|View full text |Cite
|
Sign up to set email alerts
|

Cell Culture System for Studying Bovine Neutrophil Diapedesis

Abstract: Neutrophils are the major defense against bacterial infection in the bovine mammary gland. Neutrophils migrate from blood into the lumen of the gland in response to inflammatory stimuli. This study describes the development of a system of cell culture that can be used to study neutrophil diapedesis through secretory and ductal mammary epithelial barriers. The culture system consists of successive layers of collagen, fibroblasts, collagen, and a confluent monolayer of secretory or ductal epithelial cells layere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 29 publications
3
31
0
Order By: Relevance
“…In a subsequent study [88], involving a greater diversity of cows, it appeared that a variability exists among animals, with generated C5a concentrations ranging from 0.6 ng/mL to 20 ng/mL in the milk from uninflamed, uninfected quarters. Concentrations of 25 and 50 ng/mL have been shown to induce the migration of bovine neutrophils through a cell culture system comprising a mammary epithelial cell monolayer [105], whereas 5 ng/mL were without an effect. These findings suggest that the amount of C5a which can be generated in the milk of certain cows could be of functional significance, whereas others would not be.…”
Section: Recruitment Of Phagocytesmentioning
confidence: 98%
See 1 more Smart Citation
“…In a subsequent study [88], involving a greater diversity of cows, it appeared that a variability exists among animals, with generated C5a concentrations ranging from 0.6 ng/mL to 20 ng/mL in the milk from uninflamed, uninfected quarters. Concentrations of 25 and 50 ng/mL have been shown to induce the migration of bovine neutrophils through a cell culture system comprising a mammary epithelial cell monolayer [105], whereas 5 ng/mL were without an effect. These findings suggest that the amount of C5a which can be generated in the milk of certain cows could be of functional significance, whereas others would not be.…”
Section: Recruitment Of Phagocytesmentioning
confidence: 98%
“…At other epithelial surfaces such as the lungs of rats, the outcome of the exposure of alveolar epithelial cells to C5a is the release of proinflammatory cytokines and the enhanced expression of the C5a receptor, leading to an enhanced phlogistic response [97]. There is some indirect evidence that mammary epithelial cells react to C5a [76,105]. If the contribution of C5a to the triggering of mammary inflammation proved true, it would be justified to address the origin of the variability of C5 concentration in milk (acquired or of genetic origin) [88], because it could have consequences on the cow'susceptibility to mastitis.…”
Section: The Biological Significance Of the Complement In Milk And Armentioning
confidence: 99%
“…Epithelial cells of the lung have been shown to possess receptors for C5a [10], but the presence of C5a receptors on the apical surface of mammary epithelial cells remains to be documented. In vitro experiments with purified bovine C5a have shown that C5a (> 25 ng/mL) provokes the migration of neutrophils through a confluent monolayer of mammary epithelial cells [18]. In vivo infusion of C5a in the teat cistern of cows also induces a moderate recruitment of neutrophils [13].…”
Section: Discussionmentioning
confidence: 99%
“…Concentrations of C5a (around 50 ng/mL) can be found in the milk of quarters suffering from clinical mastitis [17]. This concentration of C5a has been shown to induce the migration of bovine PMN through a confluent monolayer of mammary epithelial cells [18]. Moreover, infusion of 65 ng of C5a into the teat cistern of cows provokes an influx of PMN [13].…”
Section: Introductionmentioning
confidence: 99%
“…Although, to our knowledge, there are no publications available, this two-compartment system could potentially be applied to mammary cells as well, studying transport or metabolism of blood borne substances across the epithelium. However, interesting applications for mammary cells of the two-compartment system have been described previously in studies of polymorphonuclear neutrophil migration (Smits et al, 1996 and and protein and plasminogen activator production in mammary epithelial cells after extracellular calcium treatment (Cheli et al, 2001).…”
Section: Cell-based Models Of the Gastrointestinal Tractmentioning
confidence: 99%